Using information and communication technologies (ICTs) to solve the repressed demand for primary dental care in the Brazilian Unified Health System due to the COVID-19 pandemic: a randomized controlled study protocol nested with a before-and-after study including economic analysis - Karina Haibara Natal; Thais Gomes Machado; Fabiana Bracco; Luiz Ivan Lemos; Maria Eduarda Vigano; Gabriela Manco Machado; Jhandira Daibelis Yampa-Vargas; Daniela Prócida Raggio; Fausto Medeiros Mendes; José Carlos Pettorossi Imparato; Edson Hilan Gomes Lucena; Yuri Wanderley Cavalcanti; et al. (BMC, 2022)
Abstract Background With the COVID-19 pandemic, thousands of children had their dental care interrupted or postponed, generating a pent-up demand for primary care. To minimize the impact of this outage, information and communication technologies (ICT) could be an alternative. The aim of this study is to elucidate the impact of implementing the ICTs in primary dental care for children on resolving the pent-up demand for primary dental care to children in the national health system service (SUS) due to the COVID-19 pandemic. Methods Different research strategies are being proposed to demonstrate such effect and extrapolating findings to a real-world context to guide further research, practice and policies: two clinical trials (one randomized controlled by the waiting list trial (RCT) and a before-and-after study), one simulation study to prospect trial results to a broader population and three economic evaluations using different effects. Children enrolled in a reference dental unit will be invited to participate in the before-and-after study for trials. The first 368 families will be randomized for the RCT to the intervention vs waiting list. All participants will receive the intervention, but the waiting list group will be assessed before the intervention is available for them. The intervention comprises standardized non-face-to-face primary dental care using the V4H platform. The problem-solving and the family's perception will be the primary outcomes set for the before-and-after study and RCT, respectively. They will be measured 2 weeks after randomization. Based on trial findings, we will develop theoretical models to estimate how the intervention could benefit the population included in the national health system.  Three economic evaluations will be carried out considering different trial effects (cost-effectiveness analyses). A societal perspective and the pandemic time horizon will be considered. Possible social impact (inequalities) will also be explored. Discussion This ongoing trial may be an essential contribution to clarify positive and negative aspects related to the use of technologies for non-face-to-face dental care for children. Trial products may bring relevant contributions to the pandemic context and the post-pandemic period. Potential benefits may be feasible to implement and preserve in the health system even in the post-pandemic period. Trial registration Clinicaltrials.gov registration NCT04798599 (registered March 2021).